Pengaruh Adopsi AI Art Generator terhadap Minat dan Kepercayaan Konsumen dalam Menggunakan Jasa Ilustrator Hyuna Media di Kota Bandung - Kurnia Saputra, Dandi; Cahyani, Leni; Suryawandani, Bethani (Lembaga Teewan Journal Solutions, 2026)
This study examines the effect of AI Art Generator adoption on consumer trust and interest in using Hyuna Media's illustration services in Bandung. Using a descriptive quantitative causal-associative approach, data from 100 respondents were collected via a 1–7 Likert questionnaire and analyzed with SEM-PLS. All constructs proved valid and reliable (AVE 0.508–0.546; Composite Reliability > 0.70). AI Art Generator Adoption had a significant positive effect on Consumer Trust (β = 0.689; p = 0.000) and Consumer Interest (β = 0.604; p = 0.000), while Consumer Trust also significantly affected Consumer Interest (β = 0.189; p = 0.044). The model explained 47.5% of the variance in Trust and 42.8% in Interest. Findings confirm that Hyuna Media's success in positioning AI as a supporting tool—rather than a replacement—for human illustrators is key to building trust that drives consumer interest.